A review on the effect of external fields on solidification, melting and heat transfer enhancement of phase change materials. (October 2020) - Wu, Yifan; Zhang, Xuelai; Xu, Xiaofeng; Lin, Xiangwei; Liu, Lu
Highlights: A review on the effect of external fields on phase change materials. The effect of four different external fields is introduced. The application of external fields is introduced. This work is focused on the effect on solidification and heat transfer. Abstract: The long phase transition time and poor thermophysical properties of phase change materials inhibits the wide application of phase change energy storage technology, which is an urgent problem to be solved. Previous research focus on internal optimization of phase change materials such as adding additives, shape-stabilized technology. This paper reviews the effect of external fields (ultrasonic wave, magnetic field, electric field mechanical vibration) on reducing nucleation time, crystal growth and enhancement of heat transfer. Both experimental and numerical research progress have been reviewed to explain the mechanism that promotes nucleation and heat transfer. In this paper, the application of phase change materials under external field conditions in different industrial fields have been introduced. Finally, according to the current research situation, insufficiency in the current research is pointed out and future prospect is also reported.